2017
DOI: 10.1097/aud.0000000000000372
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Different Electrode Configurations for the oVEMP With Bone-Conducted Vibration

Abstract: This study showed the possible benefits from alternative electrode configurations for measuring bone-conducted-evoked oVEMPs in comparison with the standard electrode configuration. The nose configuration seems promising, but further research is required to justify clinical use of this placement.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
40
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(46 citation statements)
references
References 30 publications
5
40
1
Order By: Relevance
“…The study by Sandhu et al (2013) introduced a bellytendon electrode montage which was shown to result in significantly larger amplitude oVEMP responses in otologically normal participants. This finding of increased amplitude responses when using the belly-tendon electrode montage was confirmed by Vanspauwen et al (2017) and Makowiec et al (2017). Such studies confirm the belief that reference contamination can result in significantly reduced amplitude responses and contamination is attributed to the location of the reference electrode relative to the active electrode.…”
Section: Discussionsupporting
confidence: 69%
See 1 more Smart Citation
“…The study by Sandhu et al (2013) introduced a bellytendon electrode montage which was shown to result in significantly larger amplitude oVEMP responses in otologically normal participants. This finding of increased amplitude responses when using the belly-tendon electrode montage was confirmed by Vanspauwen et al (2017) and Makowiec et al (2017). Such studies confirm the belief that reference contamination can result in significantly reduced amplitude responses and contamination is attributed to the location of the reference electrode relative to the active electrode.…”
Section: Discussionsupporting
confidence: 69%
“…This electrode montage is referred to as the ''bellytendon'' montage. Sandhu et al (2013), Vanspauwen et al (2017), and Makowiec et al (2017) obtained significantly larger amplitude responses measured with the belly-tendon montage in otologically normal participants compared with amplitudes measured with the infraorbital montage. This belly-tendon electrode montage is felt to be optimal because of the lessened likelihood of reference contamination as the inverting electrode is placed over a tendon, which is believed to be electrically neutral (Piker et al, 2011).…”
mentioning
confidence: 94%
“…Contamination from other muscles may weaken the laterality of the reflex and reduce its clinical utility. The standard closely-spaced differential montage is associated with smaller amplitudes than montages with reference located much further away; for example, on the chin (Piker et al, 2011, Zuniga et al, 2014), sternum (Vanspauwen et al, 2017) or earlobes (Rosengren et al, 2005). This is because the standard montage prioritizes specificity over amplitude (some of the IO signal will be subtracted out, but so will activity from nearby extraocular muscles).…”
Section: How To Record Ovempsmentioning
confidence: 99%
“…There have been recent reports of greater oVEMP amplitudes using more lateral active recording electrodes in normal subjects, with reference electrode located either beneath the eye (Govender et al, 2016) or on the medial canthus (Sandhu et al, 2013, Makowiec et al, 2017, Vanspauwen et al, 2017). However, Piker et al (2018) showed that the medial canthus is not an electrically indifferent site.…”
Section: How To Record Ovempsmentioning
confidence: 99%
“…Cervical and ocular vestibularevoked myogenic potentials (cVEMP/oVEMP) were measured to assess saccular and utricular function, respectively (55,56). When responses were seen at or below 100 dB Hearing Level during (air conducted) cVEMP testing, saccular function was considered to be present, otherwise absent (55). For (bone conducted) oVEMP stimulation, this normal value is ≤140 dB Force Level (56).…”
Section: Clinical Evaluationmentioning
confidence: 99%